The contradition between the State and the guarantee of rights in the current capitalism crisis context (Research, Society and Development, 2020)
This article aims to discuss the contradiction between the State and the guarantee of rights in the current context of the crisis of capitalism. It is a qualitative bibliographic research. The article first presents the modern state and the institutionalization of rights and then the crisis of capitalism and the attack on social rights, specifically in the Brazilian context. As a result, the understanding obtained indicates that in capitalism, in conforming the democratic rule of law, contradictorily it is also responsible for reducing rights as a strategy to overcome the crisis, that is, it does not alter the fundamental contradictions of capitalist sociability.